Effect of feeding frequency on diurnal variation in plasma and urinary purine derivatives in steers - Chen, X.B.; Grubic, G.; Orskov, E.R.; Osuji, P.O. (Cambridge University Press, 1992)
The diurnal changes in plasma concentration and urinary excretion of purine derivatives (PD) were examined in 4 steers given feed in 1 or 2 meals daily in 2, 18-day periods. In period 1, 2 steers were fed once daily (at 08.00 h) and the other 2 twice daily (at 08.00 and 16.00 h). In period 2, the treatments were switched. In the last 4 days of each period, plasma samples were taken from 08.00 to 24.00 h at 2 to 3-h intervals, and daily urine was collected in several 4 to 8-h periods. With once daily feeding, allantoin concentration in plasma varied from 0.90 to 1.07 of the daily mean and with twice daily feeding, from 0.97 to 1.05 of mean. The coefficient of variation (CV) for total variation was 0.14. In urine, the concentration and hourly excretion of PD varied with sampling times (P 0.05) but the ratio of PD to creatinine was relatively constant even for once-daily feeding (CV, 0.02 for measurements at different times). The CV for total variation in the ratio was 0.19. The results suggest that diurnal variation in plasma allantoin concentration and in the ratio of allantoin (or total PD) to creatinine are relatively small even for once daily feeding. It thus seems that these measurements in spot samples may be suitable for use as a simple index of microbial protein supply if they are correlated with the daily PD excretion. The results also indicate that measurements in samples of plasma and urine taken between 15.00 and 20.00 h tended to give a better representation of the daily mean.